A History of Ideological Transparency. Issue 4 (2nd October 2019) - Torssonen, Sami
Abstract : Transparency has been used as a metaphor for direct social perception since antiquity. This essay studies variations in transparency rhetoric as ideological elements of broader social changes. In the eighteenth century, an individualist form of transparency language emerged with the spread of commodity production. In the mid twentieth century, bureaucratization associated "transparency" with a planned individualization that worked to mask, legitimize, and facilitate undemocratic bureaucratic control. This essay argues that Marxists should learn to recognize and avoid such misleading connotations and outline their own theory of transparency.